Discovery of a selective c-MET inhibitor with a novel binding mode. (1st November 2022) - Collie, Gavin W.; Barlind, Louise; Bazzaz, Sana; Börjesson, Ulf; Dale, Ian L.; Disch, Jeremy S.; Habeshian, Sevan; Jetson, Rachael; Khurana, Puneet; Madin, Andrew; Michaelides, Iacovos N.; Peng, Ling; et al.
Graphical abstract: Abstract: The c-MET receptor tyrosine kinase has received considerable attention as a cancer drug target yet there remains a need for inhibitors which are selective for c-MET and able to target emerging drug-resistant mutants. We report here the discovery, by screening a DNA-encoded chemical library, of a highly selective c-MET inhibitor which was shown by X-ray crystallography to bind to the kinase in an unprecedented manner. These results represent a novel mode of inhibiting c-MET with a small molecule and may provide a route to targeting drug-resistant forms of the kinase whilst avoiding potential toxicity issues associated with broad kinome inhibition.